The Contribution of Livestock to the Economies of Kenya, Ethiopia, Uganda and Sudan - IGAD Center for Pastoral Areas & Livestock Development (ICPALD) (IGAD Center for Pastoral Areas & Livestock Development (ICPALD), 2013)
Livestock specialists frequently argue that livestock production is underrepresented in the GDP estimates of African nations. With respect to Kenya, Uganda, Ethiopia and Sudan – the countries covered in this review – this argument has been confirmed. From 2010 to 2012 IGAD undertook a reappraisal of the contribution of livestock to the national economies of these four IGAD member countries. The ‘headline’ result of this evaluation is summarized in Table 1. Using 2009 as a base year for comparison, the re-estimated value added to national GDP by livestock was, depending on the country in question, 19% to 150% higher than official estimates for that year, and the monetary value added by livestock ranged from a low of over half a billion US dollars in Uganda to over fourteen and a half billion US dollars in Sudan, totaling more than 23 billion US dollars for the four countries combined. This new regional estimate represented a 37% increase in value added over the combined official estimates in 2009 for the countries concerned. Clearly livestock are big business in East Africa – much bigger, in fact, than had been previously suspected.